2016
DOI: 10.1016/j.ygcen.2016.07.013
|View full text |Cite
|
Sign up to set email alerts
|

A test of reactive scope: Reducing reactive scope causes delayed wound healing

Abstract: Reactive scope predicts that all animals have an adaptive ability to respond to stressors in their environment, termed reactive homeostasis, and that only when an animal's response to stressful stimuli exceeds a certain threshold (homeostatic overload) will stress have pathological effects. While this framework has successfully helped interpret effects of stressors on wildlife, no study has designed an experiment to directly test this framework. This study was designed to expose house sparrows (Passer domestic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 42 publications
3
28
0
Order By: Relevance
“…The experimental design was based on prior chronic stress studies that indicated that the hormonal effects of chronic stress are typically initiated within 8–12 days (Awerman & Romero, ; Cyr et al, ; DuRant, Arciniega, Bauer, & Romero, ; Gormally, Wright‐Lichter, Reed, & Romero, ; Lattin & Romero, ). In several of these studies, birds were exposed to different stressors at four different unpredictable times throughout the day for up to 3 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental design was based on prior chronic stress studies that indicated that the hormonal effects of chronic stress are typically initiated within 8–12 days (Awerman & Romero, ; Cyr et al, ; DuRant, Arciniega, Bauer, & Romero, ; Gormally, Wright‐Lichter, Reed, & Romero, ; Lattin & Romero, ). In several of these studies, birds were exposed to different stressors at four different unpredictable times throughout the day for up to 3 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…A mitotane injection at the same dose as used here was previously shown to reduce plasma CORT for up to 10 days in adult male house sparrows (Breuner et al, 2000) and mitotane treatment inhibits CORT production in mammals (Chortis et al, 2012) and birds (Jonsson et al, 1994;DuRant et al, 2016). To counter potential problems of glucose mobilization resulting from low plasma CORT and to standardize the feeding regimen, we supplemented all birds, regardless of treatment, with fresh Nektar solution (13 g 100 ml −1 0.9% NaCl in water; Nekton, Germany) daily during the 10 days following injections of mitotane or vehicle.…”
Section: Mitotane Preparation and Treatmentmentioning
confidence: 74%
“…Increased steroid hormone secretion rates during the postnatal development in SFA males were followed by a significantly higher mortality rate during adulthood. N-3 PUFA metabolites such as eicosanoids 46 and glucocorticoids in general 47 exert anti-inflammatory actions, whereas n-3 PUFA deficiencies and HPA-axis dysfunctions may profoundly impair the immune system and inflammatory responses 48 , 49 . Although the cause of deaths in SFA males was not investigated in this study, their highly increased cortisol concentrations may indicate a detrimental chronic stress state 49 , 50 .…”
Section: Discussionmentioning
confidence: 99%
“…N-3 PUFA metabolites such as eicosanoids 46 and glucocorticoids in general 47 exert anti-inflammatory actions, whereas n-3 PUFA deficiencies and HPA-axis dysfunctions may profoundly impair the immune system and inflammatory responses 48 , 49 . Although the cause of deaths in SFA males was not investigated in this study, their highly increased cortisol concentrations may indicate a detrimental chronic stress state 49 , 50 . This is usually accompanied by impaired glucocorticoid receptor sensitivity or even a resistance to cortisol, which is suggested to negatively affect HPA-axis responses to immune challenges, impair homeostasis, and increase the disease risk 49 , 51 , 52 .…”
Section: Discussionmentioning
confidence: 99%